PRINSIP TANGGUNG JAWAB PENGANGKUT DAN ASURANSI GANTI RUGI TERHADAP KORBAN KECELAKAAN PENUMPANG UMUM DI JALAN RAYA - Mig Irianto Legowo (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2019)
Responsibility of Carriers for accident victims on the highway and how the process of providing compensation by PT Persero Raharja insurance services, as well as problems that arise in the maintenance of obtaining compensation insurance (compensation). The type of research used is normative juridical research type. The analytical method used is a qualitative normative data analysis method. The results of the study can be concluded: 1) Responsibility for the error of the Carrier is carried out as a family. While compensation for PT. (Pesero) Jasa Raharja's Loss Insurance is determined by the way of handling, namely by the way the victim or heir comes to Jasa Raharja's office to request the K1 form (for accidents hit by a motor vehicle) or K2 (for public passenger accidents), which is filled in correctly and fulfills conditions: information on road traffic accidents by the police, doctor's statement, and heir's statement if the victim dies and if the conditions are met correctly then the implementation of compensation will be able to run smoothly, provided it is guaranteed by Law No. 34 of 1964 jo. PP No. 18 of 1965. 2). The obstacles that exist in the implementation of Law No. 34 of 1964 concerning: Road Traffic Accident Funds are derived from victims or heirs of the victims in the form of community reluctance to take care of claims for compensation, this is due to the fear of dealing with authorities or state officials